MANAJEMEN PEMBINAAN SANTRI DI PONDOK PESANTREN SALAF: ANALISIS SISTEM PEMBELAJARAN PONDOK PESANTREN AS-SALIMIYYAH MLANGI - Adibatunabillah, Suko Rina; Ridla, Muhammad Rosyid (UIN Sunan Kalijaga, 2025)
Salaf Islamic boarding schools are traditional Islamic da‘wah institutions that play an important role in the development of students through a learning system based on the study of classical Islamic texts. Amid the growing tendency of Islamic boarding schools to integrate formal education, Pondok Pesantren Salaf As-Salimiyyah Mlangi consistently maintains a salaf-based learning system and restricts its students from attending upper secondary formal education, with the aim of enabling them to focus fully on pesantren learning materials. This study aims to analyze the management of student development at Pondok Pesantren Salaf As-Salimiyyah Mlangi through the learning system implemented. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews with the kiai, observation of religious learning activities, and documentation analysis. The findings indicate that student development management is implemented through a structured and tiered learning system, including class organization based on the texts studied, the application of traditional learning methods such as sorogan and bandongan, and evaluation processes that emphasize mastery of classical texts and religious practices. Student development is further strengthened through supporting activities such as bahtsul masā’il and habituation of worship, which function to shape character, discipline, and students’ readiness as da‘wah cadres within society. These findings demonstrate that the Salaf pesantren learning system serves as an effective instrument of student development management within the context of Islamic da‘wah without integrating formal education.